2018
DOI: 10.1039/c8ra00824h
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and local electrical behavior in [(Nd2Ti2O7)4/(SrTiO3)n]10 (n = 4–8) superlattices

Abstract: Artificial [(Nd 2 Ti 2 O 7 ) 4 /(SrTiO 3 ) n ] 10 superlattices (n ¼ 4 and 8) were successfully epitaxially grown on SrTiO 3 substrates by pulsed laser deposition using the in situ high energy electron diffraction reflection diagnostic. Scanning transmission electron microscopy energy dispersive spectroscopy analysis showed the diffusion of Nd 3+ cations on Sr 2+ sites in SrTiO 3 structure into the multilayers, which was more pronounced when the value of n was lower. These particular nanoscale electrical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The idea of using La 0.7 Sr 0.3 MnO 3 as a thermometer was also discussed by Wu et al, who also measured the CMR effect of their samples, but did not mention its potential application in health monitoring [157]. Carlier et al mentioned that several perovskites showing CMR are lead-free which enables, in principle, their use in vivo, but without giving examples of their health monitoring applications [158]. Besides these and very similar studies, no mentions of health monitoring in correlation with CMR were found.…”
Section: Colossal Magnetoresistance Health Monitoringmentioning
confidence: 99%
“…The idea of using La 0.7 Sr 0.3 MnO 3 as a thermometer was also discussed by Wu et al, who also measured the CMR effect of their samples, but did not mention its potential application in health monitoring [157]. Carlier et al mentioned that several perovskites showing CMR are lead-free which enables, in principle, their use in vivo, but without giving examples of their health monitoring applications [158]. Besides these and very similar studies, no mentions of health monitoring in correlation with CMR were found.…”
Section: Colossal Magnetoresistance Health Monitoringmentioning
confidence: 99%